Changes of Photosynthesis Efficiency during the Process of Modern Maize Breeding - Ma Yingying (BIO Web of Conferences)
Crop yield has always been an important problem in solving the demand of the global population increase and food supply. In addition to increasing planting density, improving crop photosynthetic efficiency is the most effective measurement to increase crop yield. Maize is the world’s largest crop with a typically high photosynthetic efficiency, however, how to further increase its photosynthetic efficiency is still largely unknown, especially since its photosynthetic efficiency change during the process of modern maize breeding has not yet been reported. In this study, several typical important photosynthetic efficiency indexes, including chlorophyll content, maximum photochemical efficiency () and actual photochemical efficiency (ΦPSII), were compared between representative inbred lines of different ages. The results showed that the chlorophyll content, Fv/Fm and ΦPSII were significantly increased with age during the modern maize breeding process, which guided the breeding and improvement of new varieties of maize with high photosynthetic efficiency.